2015
DOI: 10.4103/0970-2113.159559
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach for lung delivery of rifampicin-loaded liposomes in dry powder form for the treatment of tuberculosis

Abstract: Background:Lung administration of antibiotics by nebulization is promising for improved treatment efficiency for pulmonary infections, as it increases drug concentration at sites of infection while minimizing systemic side effects. For poorly soluble molecules like rifampicin, lipid particulate system may improve lung delivery.Materials and Methods:We investigated rifampicin-loaded freeze-dried liposomes. Various formulations were prepared with different drug lipid ratios and one formulation was optimized. Opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(37 citation statements)
references
References 23 publications
0
33
1
2
Order By: Relevance
“…Patil et al 39 observed a decrease in the rate of RIF release as cholesterol content increased, whereas in these studies no major difference was observed in the kinetics of RIF release for the liposome formulations tested (Fig. 5).…”
Section: Drug Release Profilementioning
confidence: 69%
See 3 more Smart Citations
“…Patil et al 39 observed a decrease in the rate of RIF release as cholesterol content increased, whereas in these studies no major difference was observed in the kinetics of RIF release for the liposome formulations tested (Fig. 5).…”
Section: Drug Release Profilementioning
confidence: 69%
“…This is consistent with the observation reported elsewhere and suggests that RIF is getting amorphous in liposomes. 39,44 The probable explanation should be the fact that RIF's molecules are deeply embedded into the lipid bilayers as suggested by Rodrigues et al 40…”
Section: Dscmentioning
confidence: 99%
See 2 more Smart Citations
“…MTB may have killed more persons than any other microbial pathogen. The inadequacy of awareness and treatment results in major health problems, where the results are complicated [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%